Post-Pandemic Social Determination of Healthcare Workers’ Health: Lessons and Challenges in Ecuador - Juan Pablo Velasco Moncayo; Lucy Baldeón Rojas; Jorge Perez-Galarza (Disease and Health: Research Developments Vol. 4, 2025)
Background: The historical and structural dynamics that connect labor and health are examined from a critical perspective based on Latin American critical epidemiology. Critical epidemiology overcomes the restrictive notion of classical epidemiology that focuses on the health-disease phenomenon from “risk factors”, focusing on the influence of economic, social, and cultural models on workers’ health. Objective: Examine the social determination of health in the healthcare community, considering working conditions and their effects during and after the SARS-CoV-2 pandemic in Ecuador. Methods: A cross-sectional study from April 2020 to December 2021 that includes data from 2398 healthcare workers at Carlos Andrade Marín Hospital in Quito, Ecuador, tested for the COVID-19 virus. Results: The social determinants of health in the healthcare collective were examined in this research along with their link to working conditions at a public hospital in Ecuador following the COVID-19 pandemic. We found that women made up 73% of the healthcare workforce. COVID-19 infected 50% of the hospital’s medical personnel during the study period, and 20% acquired the virus again. The most frequently affected direct exposure groups were nursing assistants (55%) and nurses (61%). Discussion: The link between work and health in an all-encompassing interpretative framework was reconsidered, considering historical processes about the standard lifestyle forced on employees (labor, consumption, gender, cultural relations, social supports, and organizational settings). Conclusion: This study challenges the dominant and reductionist paradigm of exposure and risk factors operating independently and examines how workers’ health is affected by harmful influences and deterioration in a dialectical process across general, specific, and individual dimensions.